Balancing Compliance and Ethics: The Dynamics of Tax Planning, Avoidance, and Evasion in Indonesia - Sabrina Fitrianti; Rr Sheilla Novita Ellysa Putri; Indra Pahala (Manunggal Halim Jaya, 2026)
Research on corporate tax strategies in Indonesia reveals a significant financial impact, with corporate tax avoidance reaching USD 4.78 billion. This study aims to comprehensively analyze the distinctions between tax planning, tax avoidance, and tax evasion, evaluate the implementation of the substance over form principle, and assess the effectiveness of anti-avoidance regulations (GAAR and SAAR). Employing a qualitative approach with a systematic literature review method, this research synthesizes secondary data from academic journals and tax regulations using thematic analysis. The findings indicate that tax planning serves as a legal efficiency strategy aligned with tax compliance theory. Conversely, tax avoidance operates in a legal gray area that violates the spirit of the law, while tax evasion constitutes an illegal act driven by agency conflicts. Furthermore, the substance over form principle is proven to be a crucial instrument for the Directorate General of Taxes (DJP) to assess the economic reality of transactions beyond formal legal structures. However, the implementation of both GAAR and SAAR faces significant challenges regarding legal uncertainty and conflicting interpretations between tax authorities and taxpayers. This study concludes that to enhance voluntary tax compliance, the government must provide detailed technical guidelines and foster transparent, balanced communication, rather than relying solely on repressive enforcement that could trigger aggressive tax countermeasures.